2012
DOI: 10.1614/wt-d-11-00112.1
|View full text |Cite
|
Sign up to set email alerts
|

Control of Morningglories (Ipomoeaspp.) in Sugarcane (Saccharumspp.)

Abstract: Morningglories are summer annual or perennial dicots, and are troublesome weeds in sugarcane cultivated in northern India. If not controlled, they may compete with sugarcane, interfere in the harvest operation, and reduce yields. Managing morningglories in sugarcane continues to be a serious challenge for sugarcane growers. Field experiments were conducted during the 3-yr period from 2007 to 2009 to evaluate herbicides applied PRE and POST for control of morningglories in sugarcane. The herbicides applied PRE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
12
0
3
Order By: Relevance
“…It has been reported that competition with Ipomoea spp. can reduce sugarcane production by 36% (Bhullar et al, 2012). Carvalho et al (2014) observed that allowing I. hederifolia plants to coexist with corn crops reduced the growth of and accumulation of macronutrients by the corn plants with negative consequences for crop productivity and serious disturbances during mechanical harvesting when the weed is fully developed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that competition with Ipomoea spp. can reduce sugarcane production by 36% (Bhullar et al, 2012). Carvalho et al (2014) observed that allowing I. hederifolia plants to coexist with corn crops reduced the growth of and accumulation of macronutrients by the corn plants with negative consequences for crop productivity and serious disturbances during mechanical harvesting when the weed is fully developed.…”
Section: Introductionmentioning
confidence: 99%
“…I. nil (L.) Roth ou corda-de-viola também foi predominante no cultivo de figueira com um IVI de 74, planta daninha anual que apresenta hastes entrelaçadas, longo ciclo de vida e competição por nutrientes que reduz a produtividade das culturas, bem como dificulta a colheita mecanizada (Bhullar et al, 2012). Além disso, é uma hospedeira alternativa do nematóides do gênero Meloidogyne (Bellé et al, 2017).…”
Section: Resultsunclassified
“…Weeds like Ipomoea spp. which germinate well in shade, under closed crop canopy, and twin around the crop plants (Bhullar et al 2012) could also be a problem in residue based CA systems. In CA, the presence of residue on the soil surface may influence soil temperature and moisture, which may affect weed seed germination and emergence patterns over the growing season.…”
Section: Management Of Emerging Weed Species In Camentioning
confidence: 99%